2018
DOI: 10.3168/jds.2017-13543
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor delta regulates lipid droplet formation and transport in goat mammary epithelial cells

Abstract: Even though recent evidence in goat mammary epithelial cells (GMEC) suggest a role of peroxisome proliferator-activated receptor delta (PPARD) in regulating lipid homeostasis, its role is not fully understood. Our hypothesis was that PPARD regulates lipid transport processes in GMEC and, thus, plays a crucial role in regulating fat formation. The PPARD was overexpressed using an adenovirus system (Ad-PPARD) with recombinant green fluorescent protein (Ad-GFP) as the control. Results revealed that overexpression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“… 28 , 56 The emerging evidence, including our data, seems to be supporting the notion that other PPARs, such as PPARδ, may also regulate CD36-mediated lipid homeostasis by promoting fatty acid uptake, transport, and lipid droplet formation. 57 Similarly, another study by Nahle et al. showed that during the fasting state, activation of PPARδ subsequently upregulated the expression of CD36 to increase fatty acid utilization in the skeletal muscle.…”
Section: Discussionmentioning
confidence: 94%
“… 28 , 56 The emerging evidence, including our data, seems to be supporting the notion that other PPARs, such as PPARδ, may also regulate CD36-mediated lipid homeostasis by promoting fatty acid uptake, transport, and lipid droplet formation. 57 Similarly, another study by Nahle et al. showed that during the fasting state, activation of PPARδ subsequently upregulated the expression of CD36 to increase fatty acid utilization in the skeletal muscle.…”
Section: Discussionmentioning
confidence: 94%
“…The mRNA abundance of CD36 was down-regulated by 56% after interfering PPARA in GMECs, which was the same as the positive regulatory effect of PPARA in the de novo synthesis of milk fat, however, interfering PPARA up-regulated the mRNA abundance of ACSL1 and also significantly increased TAG content, suggesting a stronger negative regulation of ACSL1 by PPARA and further interpreting the dominance of LCFA uptake in the blood ( 37 ). Several studies have confirmed that t10c12-CLA, PPARG and PPARD exhibit positive regulation of both CD36 ( 35 , 87 , 106 ) and ACSL1 ( 34 , 36 , 63 ), however, Shi et al ( 61 ) challenge the above view that t10c12-CLA A positively regulates CD36 and ACSL1, which may be related to factors such as the species, mode and amount of additives, the exact mechanism of action needs to be further verified by more in-depth experimental studies as well as large-scale populations. As previously described, 14-3-3γ, LXR, SREBP1 and CIDEC have positive regulatory roles in the de novo synthesis of milk fat, which perform similar functions during LCFA uptake ( 21 , 29 , 36 , 69 ).…”
Section: Lcfa Uptake and Activationmentioning
confidence: 92%
“…Twelve hours before treatment with the leucine-containing medium, BMECs were treated with WY14643 in an amino acid-free medium and the cells were cultured with dimethyl sulfoxide (DMSO) serving as control. PPARα was overexpressed using an adenoviral system as described previously . BMECs were incubated with the adenovirus medium Ad-PPARα and Ad-GFP.…”
Section: Methodsmentioning
confidence: 99%
“…PPARα was overexpressed using an adenoviral system as described previously. 20 BMECs were incubated with the adenovirus medium Ad-PPARα and Ad-GFP. After treatment, BMECs were harvested for RNA analysis, cholesterol assay, and other experimental examinations.…”
Section: Primary Bovine Mammary Epithelial Cell Isolation Cellmentioning
confidence: 99%